The impact of loneliness on quality of life in people with Parkinson’s disease: results from the Survey of Health, Ageing and Retirement in Europe - Prell, Tino; Schönenberg, Aline; Heimrich, Konstantin G. (Frontiers in Medicine, 2023)
Background: Loneliness is a growing issue for public health in an aging society. However, there is a lack of research on loneliness in people with Parkinson's disease (PwPD). Methods: We analyzed cross-sectional and longitudinal data from wave 5 (N = 559 PwPD) and 6 (N = 442 PwPD) from the Survey of Health, Ageing and Retirement in Europe (SHARE). Loneliness was assessed using the three-item version of the Revised UCLA Loneliness Scale. Descriptive statistics, group comparisons, multiple linear regressions, and generalized estimating equation analysis were performed to explore loneliness prevalence, its relationship with other factors, and its impact on Quality of Life (QoL) in PwPD. Results: Depending on the used cut-off, the prevalence of loneliness in PwPD ranged from 24.1% to 53.8%. These prevalences were higher compared to people without PD. Loneliness was mainly linked to decreased functional abilities, weaker grip strength, more symptoms of depression, and country of residence. Loneliness was also associated with current QoL and predicts future QoL in PwPD, highlighting its impact on well-being. Conclusion: Addressing loneliness could potentially improve QoL for PwPD, making it a modifiable risk factor that clinicians and policy-makers should consider.